Figuring Korean futures : children's literature in modern Korea - Zur, Dafna (Stanford University Press, 2017)
In the 1920s, a narrator-adult voice began to speak for the first time directly to a child-reader whose mind was deemed knowable and moldable. Writers and educators saw the qualities of this unique child audience manifest in a new concept called the child-heart, or tongsim. This text examines children's literature at the moment the child emerged as a powerful metaphor of Korea's future, through the colonization of Korea, and up until the ideological entrenchment that intensified in the post-liberation period.